Diagnostic clarification, new morphological data and phylogenetic placement of Amphisbaena arenaria Vanzolini, 1991 (Amphisbaenia, Amphisbaenidae) - Teixeira, Mauro Junior; Vechio, Francisco Dal; Rodrigues, Miguel Trefaut (Zootaxa, 2016)
Several decades ago, Vanzolini (1991) described Amphisbaena arenaria Vanzolini, 1991 based on a single individual (MZUSP 65817) collected at Raso da Catarina, a large flat sandy deposit at the southern bank of São Francisco River. In the same paper he described A. frontalis Vanzolini, 1991 based on specimens collected at another sandy area, at the northern bank of São Francisco River, both in Bahia state, Brazil. As conflicting values are presented throughout his paper, the diagnosis of A. arenaria still needs clarification. We here comment on these differences and re-diagnose A. arenaria including new topotypic material, providing its phylogenetic placement and a new state record.